Critical Thinking in the Nursing Profession: Analysis with a Socratic Method and Nurse Theorist Philosophy - Badil; Najma Naz; Mehrin Kausor (Journal of University Medical & Dental College, 2023)
Critical thinking skills are increasingly imperative skills in the nursing profession. Both the Socratic method and nursing theorist philosophy can lead to enhance critical skills. The Socratic method has been rooted in ancient Greek Philosophy, whereas nursing theorist philosophy in the 21st century. This paper discusses critical thinking in the nursing profession and compares the critical thinking concept with the Socratic Method and nurse theorist philosophy. The prime aim of this study is to compare which method is effectively utilized in the nursing profession. The literature pertinent to the topic was searched using the database library, including PubMed, BioMed, Google Scholar, PakMediNet, and Cumulative Index to Nursing and Allied Health Literature CINAHL. Literature was searched using keywords including Socratic method, nurse theorist philosophy, critical thinking skills, nursing education, and nursing clinical practice. The full-text article was included in the study. Relevant original articles, systemic reviews, quasi-experimental design, philosophical papers, and cross-sectional studies focusing on nurses' critical thinking skills, the Socratic Method, and nurse theorist philosophy were included. The study analysis portrayed Socratic questioning as primarily embedded in critical thinking concepts which nurses utilized in theoretical knowledge. The Socratic Method is explicitly known as the student-centered method that probes critical thinking in classroom teachings. Critical thinking has become vital in professional accountability and excellent nursing care. Nurse theorists have generally employed critical thinking skills to obtain the maximum patient care outcome. In conclusion, the Socratic method increases critical thinking in academia while nursing’s theorist philosophy in nursing clinical practice.